Assessment of Morphological Characteristics of Indigenous Chicken Ecotypes of Kenya - Chesoo, B. K.; Wanga, J. O.; Nandwa, A. (Africa Environmental Review Journal, 2021)
Poultry mainly consist chicken (Gallus gallus domesticus) with varied morphological appearances. The amplified global use of highly prolific breeds leads to a loss of inherent genetic diversity in indigenous chicken (IC) ecotypes. Description of ecotypes provides data on present and impending future uses of IC ecotypes populations. The study was conducted at University of Eldoret, commercial Farm using six IC ecotypes of Kenya based on selected phenotypic characters. The study was conducted using eggs sourced for hatching from agro ecological zones and the chicks were reared under deep litter production system for 14 weeks. sample size totalled 87 birds distributed as follows: Nandi (ND,10), Elgeyo Marakwet (EM,17), Turkana (TR,20), Lamu (LM,10), Homa Bay (HB,10), Meru (MR, 10) and KARI improved (KR,10). Data on morphological body parameters was collected at week 14 of age. Chi square test (χ2) in SPSS (Version 20) was used to test for any significant difference in percentages (α=5%). Plumage colour, majority (60%) of KR ecotype chickens were either blue with red (20%), blue and red (20.0%) and either blue mixed with white or brown (20%) (χ2= 12.00, d.f. =6, P = 0.0620). For the EM ecotype, majority of chicken plumage was blue with brown (47.1%) (P< 0.05). In TR ecotypes, a significant percentage (χ2= 296.28, d.f.=7, P = 0.0000) had black with white coloured plumage. HB ecotype, a higher significant proportion (χ2= 26.0, d.f.=6, P=0.0002) had black with white and brown coloured plumage (30.0%). A large proportion of chicken had yellow coloured shank. These were from KR (100%), TR (61.9%), HB (80.0%), MR (80.0%) and ND (50.0%). As far as comb type was of concern, all KR and HB ecotypes had single comb type (100%). All KR, TR, LM and MR IC ecotypes had normal head type while in EM ecotype, a lower significant proportion (χ2= 77.44, d.f.=1, P= 0.0000) had crested head type (5.88%). In conclusion, the study indicated presence of a substantial variety in morphological characteristics between and among the Kenya chicken ecotypes. More phenotypic and genetic facts that involves all qualities and all ecotypes of Kenya together with the role of the traits and the principal genes on socio-economic factors should be evaluated to abundantly characterize them in order to use in advancement of their use, preservation of genetic variability and regulate further gene dilution.